Green Entrepreneurship and Branding in Developing Economies: A Data-Driven Analysis - *Dr. Muhammad Hashim Khan; Dr. Shakeel Khan; Dr. Shahid Iqbal (Review Journal of Social Psychology & Social Works, 2025)
The past decade has seen a rising emphasis on sustainability and environmental awareness in business worldwide. In developing economies, entrepreneurs are increasingly launching green ventures businesses whose products, services or operations explicitly aim to benefit the environment. These green entrepreneurs must often communicate their environmental credentials effectively to succeed, making branding and marketing a crucial part of their strategy. This paper examines how green startups in emerging markets brand themselves, which branding strategies resonate with consumers, and how market trends support (or hinder) green ventures. We draw on real, publicly available data from market research surveys, industry reports, and global datasets to explore these questions in the context of developing countries (especially South Asia and Africa). In particular, we analyze consumer attitudes, market size and growth of eco-friendly products, and examples of brand positioning. The findings aim to guide entrepreneurs and policymakers in using data-driven branding approaches for sustainability.